Incidence and risk factors for persistent symptoms in adults previously hospitalised for COVID-19 - Munblit, D; Bobkova, P; Spiridonova, E; Shikhaleva, A; Gamirova, A; Blyuss, O; Nekliudov, N; Bugaeva, P; Andreeva, M; DunnGalvin, A; Comberiati, P; Apfelbacher, C; et al. (Wiley, 2021)
Background: The long-term sequalae of COVID-19 remain poorly characterized. We assessed persistent symptoms in previously hospitalized patients with COVID-19 and assessed potential risk factors.